2020
DOI: 10.1186/s13256-020-02526-2
|View full text |Cite
|
Sign up to set email alerts
|

Double-hit lymphoma of the male breast: a case report

Abstract: Background Whereas lymphoma of the female breast is already rare, lymphoma of the male breast has only anecdotally been reported. Within a study of 32 lymphoma of the breast reported between 1973 and 2014 as Burkitt lymphoma, we observed a single male case, which we report here. Case presentation A 72-years-old Caucasian man presented with a mass in his left breast. Clinical history included prior basal cell carcinoma, leiomyosarcoma, and administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Reports describing the molecular features of male PBL are scarce. Only Shaymaa Elgaafary et al [ 17 ] reported a case of male breast high-grade B cell lymphoma with MYC and BCL2 rearrangement, and genome-wide chromosomal imbalance mapping revealed a complex pattern of aberrations, including copy-number gains in chromosomes 3q and 18 and focal homozygous loss in 9p21.3, resembling typical changes of lymphomas affecting “immune-privileged” sites.…”
Section: Introductionmentioning
confidence: 99%
“…Reports describing the molecular features of male PBL are scarce. Only Shaymaa Elgaafary et al [ 17 ] reported a case of male breast high-grade B cell lymphoma with MYC and BCL2 rearrangement, and genome-wide chromosomal imbalance mapping revealed a complex pattern of aberrations, including copy-number gains in chromosomes 3q and 18 and focal homozygous loss in 9p21.3, resembling typical changes of lymphomas affecting “immune-privileged” sites.…”
Section: Introductionmentioning
confidence: 99%
“…Wiseman and Liao confirmed the definition of PBL in 1972, including the following criteria: (1) sufficient tumor tissue for histological examination; (2) no previous lymphoid malignancy at regions outside the breast; (3) lymphoma primarily presented within breast regions; and (4) close associations between lymphoma and breast tissue (5). This infrequent tumor was found especially in females, and quite uniquely, there were a few case reports in males in previous literature studies (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Due to the extreme rarity and unspecific manifestations, male patients with PBL are easily misdiagnosed clinically, thus delaying the optimal treatment time window and causing great pain to patients during the period of seeking medical advice.…”
Section: Introductionmentioning
confidence: 79%
“…While females constitute a majority of PBL patients (95%–100%) ( 25 ), male patients are extremely few in number. Less than 50 cases of male patients have been reported, and none of the cohorts of male PBL has been analyzed in previous literature studies ( 11 ). Thus, this study first conducted a comprehensive clinical analysis of PBL with the largest cohort of 122 male patients taken from the SEER database who were diagnosed between 2000 and 2019.…”
Section: Discussionmentioning
confidence: 99%
“…It presents histologically as a diffuse infiltrate of medium-sized B cells, with a uniform growth pattern, which forms a characteristic “starry sky” appearance 27 ( Figure 4 A). Immunohistochemically, PB-BL is positive for CD20, as well as for the germinal centre markers CD10 and BCL6 27 , 30 , 31 ( Table 2 ) and are almost exclusively 100% positive for Ki67 ( Figure 4 B), highlighting the high proliferative capacity of PB-BL. 30 Both this high proliferation index and the presence of a chromosomal breakage and translocation of the MYC locus in over 90% of PB-BL cells 27 , 30 are characteristic of all forms of BL, not just those localised to the breast.…”
Section: Primary Breast Lymphoma Of a B Cell Originmentioning
confidence: 98%
“…29 , 30 There have been reports, albeit very rarely, of males developing PB-BL; one case described a male with a history of basal cell carcinoma and spironolactone (anti-androgen) treatment presenting with high-grade PB-BL. 31 Interestingly the common denominator in these cases is a history of a significant hormonal alteration, thus suggesting a role for hormonal changes in the development of PB-BL.…”
Section: Primary Breast Lymphoma Of a B Cell Originmentioning
confidence: 99%